Understanding exposure risk using soil testing and GIS around an abandoned asbestos mine - Abhijeet V. Jadhav; Nilesh Gawde; Ramesh Veerappan; Yeyong Choi; Arthur L. Frank (Annals of Global Health)
Background: Abandoned asbestos mines are a potential source of environmental contamination and exposure for nearby residents. The asbestos exposure risk may persist even after the cessation of mining activity if the mine is not properly closed. One such abandoned mine is at Roro Hills in the Jharkhand state of India. There are limited studies examining soil contamination and asbestos exposure to nearby residents due to abandoned mines. Objectives: The aim of this study is to examine the presence of asbestos in the residential areas of villages surrounding an abandoned asbestos mine and to understand the spread of visible asbestos dust using geographic information system map analysis. Methods: This study examined the presence of asbestos in soil samples from four villages surrounding an abandoned asbestos mine using the scanning electron microscopy technique. The study also compared satellite images taken 13 years apart to determine whether the mine waste containing asbestos had spread over time. Findings: The soil sample testing indicated that, out of 16 soil samples from residential areas, 12 showed the presence of chrysotile asbestos. It was found in the map analysis that asbestos-containing areas had enlarged by around 20% in those years. Conclusion: The evidence indicated the presence of asbestos in the soil of nearby residential areas around the mine, and this contamination has spread over the years. Similar studies at other mine locations are needed, and timely interventions are warranted to protect nearby residents.